2015
DOI: 10.3791/52107
|View full text |Cite
|
Sign up to set email alerts
|

Live Imaging of Innate Immune and Preneoplastic Cell Interactions Using an Inducible Gal4/UAS Expression System in Larval Zebrafish Skin

Abstract: Here we describe a method to conditionally induce epithelial cell transformation by the use of the 4-Hydroxytamoxifen (4-OHT) inducible KalTA4-ER T2 /UAS expression system 1 in zebrafish larvae, and the subsequent live imaging of innate immune cell interaction with HRAS G12V expressing skin cells. The KalTA4-ER T2 /UAS system is both inducible and reversible which allows us to induce cell transformation with precise tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 25 publications
(26 reference statements)
0
18
0
Order By: Relevance
“…Subsequent zebrafish studies have shown a similarly rapid recruitment of neutrophils and/or macrophages to the skin, liver and brain in response to transgenic expression of numerous oncogenes, e.g. HRAS G12V , KRAS G12V , NRAS Q61K , Src, Xmrk, Myc and Akt [6,7,[39][40][41]60,68,104,[140][141][142][143]. Live imaging has provided insight into the dynamics of the intrinsic inflammatory response following tumour initiation within these models.…”
Section: Zebrafish Studies Reveal Leukocyte Recruitment and Trophic Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent zebrafish studies have shown a similarly rapid recruitment of neutrophils and/or macrophages to the skin, liver and brain in response to transgenic expression of numerous oncogenes, e.g. HRAS G12V , KRAS G12V , NRAS Q61K , Src, Xmrk, Myc and Akt [6,7,[39][40][41]60,68,104,[140][141][142][143]. Live imaging has provided insight into the dynamics of the intrinsic inflammatory response following tumour initiation within these models.…”
Section: Zebrafish Studies Reveal Leukocyte Recruitment and Trophic Fmentioning
confidence: 99%
“…However, inducible systems for transgene expression have been appropriated from the Drosophila and mouse fields, including the Tet/On system [35], the Lex/PR system [36], the tamoxifen-inducible GAL4/UAS system [37] and the heat-shock-inducible Cre/Lox system [38]. These systems have recently been used to develop inducible cancer models, which now enable temporal precision for the study of tumour initiation in both larval and adult fish (see Table 1) [25,[39][40][41].In addition to the use of zebrafish for the study of cancer biology, the zebrafish has also been widely used for the study of haematopoiesis [42] and the innate immune response [43][44][45]. Both macrophages and neutrophils share comparable developmental origins with their mammalian counterparts [46][47][48][49], and exhibit a high degree of functional conservation, for example, with respect to host-pathogen interactions [50] and wound healing [51,52].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, inducible systems for transgene expression have been appropriated from the Drosophila and mouse fields, including the Tet/On system [33], the Lex/PR system [34], Tamoxifen-inducible GAL4/UAS [35] and heat-shock inducible Cre/Lox [36]. These systems have recently been used to develop inducible cancer models, which now enable temporal precision for the study of tumour initiation in both larval and adult fish [37][38][39][40][41].…”
Section: Zebrafish Transgenic Models Of Cancer For In Vivo Live Imagimentioning
confidence: 99%
“…Already, using transgenic reporters in a zebrafish KRAS G12D pancreatic model of cancer, it is proving possible to live image the signalling activities -for example TGFβ, Notch, bone morphogenetic protein (BMP) and sonic hedgehog (SHH) signalling -of transformed cells 47 . By crossing lines expressing the right combinations of reporters in both immune cells and pre-neoplastic cells 48 , it will be possible to observe both sides of the signalling interaction as immune cells first encounter cancer cells. It will be essential to understand how the trophic inflammatory phenotype is first triggered in immune cells.…”
Section: Future Directions Imaging Signalling Interactionsmentioning
confidence: 99%